Relationship between Soil Properties and Fruit Yield of New Actinidia arguta (Siebold & Zucc.) Planch. ex Miq. Cultivars in South Korea - Ha, Si-Young; Jung, Ji-Young; Park, Jai-Hyun; Yang, Jae-Kyung (Journal of Agriculture & Life Science, 2020)
Soil properties are important environmental conditions affecting fruit quality and yield in new cultivars of Actinidia arguta. The yield of three A. arguta cultivars (cv. Autumn Sense, cv. Chungsan, and cv. Greenball) from Wonju city, South Korea was investigated from 2017 to 2019 and the relationships to soil properties are discussed. The yield of cv. Autumn Sense, cv. Chungsan, and cv. Greenball fruits ranged from 6.8 to 24.5, 14.0 to 29.0, and 10.5 to 38.5 kg/vine. cv. Autumn Sense had the highest soil organic matter content and soil C/N ratio over the three-year period. The yield of A. arguta fruits was positively correlated with soil C/N ratio and could be described by a power model (y = axb), suggesting that soil C/N ratio plays an important role in limiting the bioavailability and bioaccumulation of organic matter in A. arguta fruits. In addition, C/N ratio in the soil was influenced by the soil available phosphate. However, the threshold of the C/N ratio for A. arguta fruit differed according to cultivar, and especially the lowest threshold was observed in cv. Chungsan. Therefore, the application of an appropriate C/N ratio depending on the cultivar is required for improved fruit yield. Our results present the soil properties required to increase the yield of the new A. arguta cultivars in South Korea.